TECHNIQUE AND DEVICE FOR THE EXPERIMENTAL ESTIMATION OF THE ACOUSTIC IMPEDANCE OF VISCOELASTIC MEDIUM - O. V. Murav’eva; V. V. Murav’ev; D. V. Zlobin; O. P. Bogdan; V. N. Syakterev; V. V. Volkov (Приборы и методы измерений)
Measuring the characteristics of process fluids allows us to evaluate their quality, biological tissues – to differentiate healthy tissues and tissues with pathologies. Measuring the characteristics of process fluids allows us to evaluate their quality, biological tissues – to differentiate healthy tissues and tissues with pathologies. One of the complex acoustic parameters is the impedance, which allows one to fully evaluate the characteristics of viscoelastic media. Most of impedance methods of measurements require using two or more reference media and the availability of calibrated acoustic transducers. The aim of this work ware introduced a methods and construction for the experimental evaluation of the longitudinal and shear impedance of viscoelastic media based on measuring the parameters of the amplitude-frequency characteristics and calculating the elements of the electric circuit for replacing the piezoelectric element which vibrating in the test medium.The paper introduces a methods and construction of the experimental evaluation of the impedances of viscoelastic media. The suggested methods is allowed measuring longitudinal and shear impedances and determining velocities of longitudinal and transverse ultrasonic waves and the values of the elastic moduli of viscoelastic media, including in various aggregate states. The technique is fairly simple to implement and can be reproduced using simple laboratory equipment.The obtained values of the acoustic impedances of the investigated media are in satisfactory agreement with their reference data. In contrast to the known methods for determining the acoustic impedance, the developed technique allows us to estimate with sufficient accuracy the parameter of the shear impedance of viscoelastic media that is difficult to measure at the frequencies of the megahertz range, which determines the shear modulus of the material and characterizes its resistance to shear deformations. The results of the implementation of the developed technique for the estimation of acoustic parameters for a number of media with zero shear elasticity (alcohol, acetone) and viscoelastic media (glycerin, architectural clay, silicone sealant and glue МР-55 before and after polymerization) are presented.